Wealth differentiation in household use and trade in non-timber forest products in South Africa - Paumgarten, F.; Shackleton, Charlie M. (2009)
Findings from southern Africa and internationally indicate the local use and trade of NTFPs to be significant however most present a composite picture, failing to account for intra-community socio-economic differences. These differences may have implications for policy and practice related to poverty alleviation and sustainable use. This paper reports on a study in South Africa which explored the relationship between household wealth and the use, procurement and sale of NTFPs in two villages. There was no influence of wealth on the proportion of households using or purchasing most of the NTFPs, or the number used. However, wealthier households bought significantly more resources per household, and poor households (at one village) sold significantly more. These results are discussed within the context of local conditions and poverty alleviation debates.